Use of mobile phones for project based learning by undergraduate students of Nigerian private universities (2012)
A university’s objective is to educate its students using information and communication technologies (ICTs) and teaching techniques that would enable its graduates become flexible and life-long learners that can easily adapt to the changes eminent in the information society. Achieving this aim requires among other factors, the adoption of appropriate teaching model such as the project based learning (PBL) which supports the inculcation of collaborative and lifelong learning skills, technology use skills, knowledge sharing skills and social networking skills into students. Consequently, this study was carried out to evaluate the use of mobile phones by students involved in PBL in three randomly selected private universities in Nigeria. The questionnaire was used as the instrument for data collection from 750 undergraduates students distributed across the three selected private universities in southwestern Nigerian states. This is to say that 250 students were sampled from each of the participating private universities whose population was estimated to be about 2000 students each. Also, the use of stratified sampling technique ensured that only those students that were in their second, third, fourth and fifth year in the sampled universities, who were presumed to have acquired required learning experiences, participated in the study. The result showed that a significant percentage of the students studied had mobile phones and that they used their mobile phones for communication, interactions, getting information, browsing the Internet, and sharing knowledge anytime they were involved in PBL. It was also revealed that mobiles phones can be used to strengthen PBL in higher institutions and can be used to implement information services provided for students in their university. Although private universities in southwestern Nigeria amounts to about 43.9% of private universities in Nigeria, a percentage that makes them a sizable representation of private universities in Nigeria, the fact that the study sampled population was drawn from only three southwestern Nigerian based private universities made generalizing the results of this study as the situation in Nigeria in appropriate. The study however, provides first hand information on the prospects, gains and challenges mobile phones offer as appropriate education technology for implementing PBL in Nigerian universities